Navigating Cultural Diversity in Mental Health Management: Global Best Practices and Challenges - Malikah; Wulandari, Citra Eka (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Cultural diversity is one of the major challenges in mental health management globally. Different cultural views on mental disorders often lead to difficulties in providing effective and appropriate care for patients with diverse cultural backgrounds. This study aims to identify the challenges of integrating cultural diversity into the mental health care system, and to assess best practices that can be implemented to improve the effectiveness of culture-based care. The method used in this study was a literature analysis, which included a review of recent studies on culturally-based mental health management in various countries. The findings revealed several key challenges, including the inability to adapt therapeutic approaches to patients’ cultural values, mental health stigma, and limitations in training and available resources. The study also found that integration between traditional medicine and Western medical approaches can improve patient acceptance of the treatment provided. Based on these findings, this study recommends the development of inclusive policies and culturally-based training programs for medical personnel, in addition to the importance of community outreach to reduce stigma towards mental disorders. It is hoped that the results of this study can contribute to improving the quality and accessibility of culturally sensitive mental health care.